Ego Eimi dalam Alam Pikiran Rasul Yohanes - Yefta Alexander Kansil (Voice, 2022)
The phrase ἐγώ εἰμι (Ego Eimi, “I am”) uttered by Jesus Christ is His unique self-confession which has theological value for Christianity in general. This self-confession is strongly emphasized in the Gospel of John. Even though this saying of Jesus is so significant in John, there are parties who falsely reinterpret the saying and thus undermine the implication of the meaning of His words. Especially among unitarian Christians, they disagree with mainstream Christians who are trinitarian regarding the meaning of Ego Eimi that Jesus uttered to support the theological presuppositions they hold regarding the identity of Jesus. Until now, the essential doctrines of Christianity are constantly being challenged by those who question them at the textual level. This research was conducted using a comparative qualitative method between the verses in the Tanakh and the LXX which represent all the words of the Ego Eimi spoken by Jesus about Himself, both absolute and equipped with nominative predicates with verses in the Old Testament which have the same linguistic and contextual features. The scope of the research object is limited only to the Gospel of John. In conclusion, this research literally indicates the equality of the Divine essences of Jesus Christ and Yahweh.